The Effectiveness of Trap Colors Against the Catch of Rice Plant Pests - Idum Satia Santi; Erick Firmansyah; Bayu Muhlin Febrian; Herry Listianto (Akademi Komunitas Perkebunan Yogyakarta, 2023)
The use of traps is one of the environmentally friendly pest controls. Insects have a preference for the colour of objects. The research aims to determine trap colours' effectiveness in catching rice plant pests. The research was conducted from June to July 2021 in Depok, Sleman Regency, Yogyakarta Special Region. The study used a descriptive observational method on an 8-week-old rice planting area. The colour traps used are white, red, green, yellow, and blue. The experiment used a completely randomized design with five replications. The results showed that the yellow trap produced the most insect catches, namely 545 insects, and the white colour produced the lowest catch of 74 heads. Pests that are heavily trapped in a row from the most to the least are Hydrelia sp, Leptocorisa oratorius, Nephotettix virescens, Pareaucosmetus sp, and Nilaparvata lugens. The most trapped is Hydrellia sp, as much as 78% of the total trapped insect pests. Effective trap installation time in the morning.